Synthesis of SnO_2 Nanorods by Hydrothermal Method for Gas Sensor Application - Trung, Khuc Quang; Hien, Vu Xuan; Vuong, Dang Duc; Chien, Nguyen Duc (Communications in Physics, 2012)
SnO2 nanorods have been successfully prepared by hydrothermal method using tin chloride, ammonia, sodium hydroxide and cetyltrimethyl ammonium bromide (CTAB) as starting materials. Structural properties and surface morphologies of the SnO2 nanorods were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The experimental results show that diameters of the nanorods are around 100 nm to 300 nm with length of several micrometers. In the preparation process of nanorods, the surfactant CTAB plays an important role in the formation and growth processes of SnO2 nanorods. The gas sensitivity experiments have demonstrated that the SnO2nanorods exhibit a good sensitivity to alcohol vapors, which may offer potential applications in the gas sensors.